Study on Uterine Environment of Buffaloes during Different Reproductive Phases - Sarvaiya, Nitesh P.; Parmar, Ajay P.; Pathan, Mohsin M.; Kumar, Sushil (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
This study was undertaken to examine the changes in composition of hormonal and biochemical constituents of uterine secretions of buffaloes (n = 35) during different phases of reproduction, i.e., proestrus, estrus, metestrus and diestrus and anestrus condition. The protein fractioning of blood and uterine secretions was carried out by Gel electrophoresis. Most of the hormonal and biochemical parameters studied revealed higher levels at the estrus phase, indicating peak metabolic activity at the time of estrus, ovulation and fertilization period. The role of enzymes and macro-micro-minerals levels are also reported and discussed. Of the 35 different protein fractions (18 to 192 kDa) observed, the numbers of protein bands present in blood sera were 15 and in uterine fluid secretions 28, of which 8 were common in both the fluids. The findings between normal cyclic and anestrus conditions may be useful to find out the cause-effect relationship of infertility in buffaloes.